Controlling dengue: an uphill task? - Amjad, Nasser Muhammad (Faculty of Medicine, International Islamic University Malaysia, 2015)
Mosquito-borne dengue viral fever is one of the fastest spreading global health hazards of recent times. Although it has been widespread especially in the tropics, dengue came into prominence since the early 1950’s following the epidemic in south East Asia. The commonest presentation of Dengue Fever is characterized by high fever, severe headaches, muscle pain and skin rash. This is the primary form and is less serious than the deadly secondary form referred to as Dengue hemorrhagic fever. The latter mainly affects most Asian and Latin American countries and has become a leading cause of hospitalization and death among children in these regions.1 It is estimated that 390 million dengue infections occur per year of which about 25% present with clinical manifestations.